Palma and the gaze theory - Arista Montoya, Luis Alberto (2023)
In this essay the Peruvian Tradition, by the Peruvian writer Ricardo Palma, entitled “La conspiración de la saya y el manto”, is analyzed in the light of the theory of the gaze exposed by the French philosopher Jean-Paul Sartre in his work “Being and Nothingness”; this analysis is based on the value and the political intentionality of the tapadas limeñas gaze, in the pre-republican Peru. Keywords: Peruvian Tradition, body, gaze, neighbor, power, social conspiracy.